2013
DOI: 10.1021/nl403047m
|View full text |Cite
|
Sign up to set email alerts
|

Giant Suppression of Photobleaching for Single Molecule Detection via the Purcell Effect

Abstract: ABSTRACT:We report giant suppression of photobleaching and a prolonged lifespan of single fluorescent molecules via the Purcell effect in plasmonic nanostructures. The plasmonic structures enhance the spontaneous emission of excited fluorescent molecules, reduce the probability of activating photochemical reactions that destroy the molecules, and hence suppress the bleaching. Experimentally, we observe up to a 1000-fold increase in the total number of photons that we can harvest from a single fluorescent molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 45 publications
6
57
0
1
Order By: Relevance
“…[ 8,16 ] Another emergent property of these systems is the improved photostability of the fl uorophores as a result of a decreased time spent in the excited state. [ 17 ] While these phenomena are interesting for the study of fundamental processes in photosynthesis, super-radiant fl uorescence is not conducive to forming charge separations necessary for photocurrent generation, and thus a more suitable design is desired in bioelectronic devices. Accordingly, we have pursued novel arrangements whereby the plasmonic interactions support the rate of charge separation, yet inhibit strong radiative and nonradiative decay.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,16 ] Another emergent property of these systems is the improved photostability of the fl uorophores as a result of a decreased time spent in the excited state. [ 17 ] While these phenomena are interesting for the study of fundamental processes in photosynthesis, super-radiant fl uorescence is not conducive to forming charge separations necessary for photocurrent generation, and thus a more suitable design is desired in bioelectronic devices. Accordingly, we have pursued novel arrangements whereby the plasmonic interactions support the rate of charge separation, yet inhibit strong radiative and nonradiative decay.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the metallic structures can convert the usual omnidirectional emission into directional emission and can modify the polarization of the coupled emission without the use of any lenses or polarizers [79]. The near-field coupling also results in spectral control on emission [10], enhanced spontaneous emission rates of molecules [11], giant suppression of photobleaching for single-molecule detection [12], and a strong fluorescence enhancement [1315]. Due to these significant advantages of near-field coupled emission, it is of great importance to investigate the factors affecting the near-field coupling interactions between fluorophores and plasmonic fields.…”
Section: Introductionmentioning
confidence: 99%
“…As the fluorophore spends less time in the excited state, the photostability will increase and thus a higher number of photons can be detected before irreversible photobleaching occurs. 27,28 To date only a few studies on emission enhancement of lightharvesting complexes have been reported using chemically synthesized metal nanostructures such as silver island films, 29,30 gold, [31][32][33] and silver nanoparticles. 34 In most studies the individual contributions of excitation and QY changes to the total fluorescence enhancement have not been disentangled.…”
Section: Introductionmentioning
confidence: 99%